Structural and Morphological Characterization of the Chromium-doped β-Spodumene to Ceramic Pigment (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The structural and morphological properties of the novel chromium-doped β-spodumene based ceramic pigment were evaluated aiming to study its chemical and thermal stability in industrial applications. The pigment samples were synthesized by the proteic sol-gel method using gelatin as a ligand. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were performed. Rietveld refinement of experimental diffractograms and average crystallites size by the Scherrer’s method analysis were carried out. XRD results confirmed that the crystal structure of lattice corresponded to β-spodumene and the Rietveld refinement indicated the absence of structural changes with doping up to 3% of chromium. Scherrer’s method indicates that there are no trends changes in the average size of crystallites in the analyzed doping contents. SEM analysis indicated that there are no morphological changes in the chromium-doped particles. The present study concluded that structural or morphological alterations are not noticed for β-spodumene samples produced with chromium doping up to 3% by weight, and that this pigment possibly preserves the chemical and thermal stability of pure β-spodumene. The absence of changes in these properties by doping with low chromium contents were attributed to possible substitutions of Al3+ by Cr3+ ions in the β-spodumene crystal lattice.